Técnicas de multiplicación de la Uña de Gato Uncaria Tomentosa (Willd) DC., bajo condiciones de cultivo In Vitro en el distrito de Morales, San Martín - Perú - Mendo Alegría, Luis Federico (2003)
With the publications made it concerning to the Uncaria tomentosa (Cat's Claw) about its healing properties, generated a Boom toward to cosume this plant such a moment, of put in danger of draining or extinction. In front of this problem we search ways to help its recovery in the woods for profit to the native communities and the consumer market. The current research, it´s design certainly for fulfill these objectives, alhuugh the used techniques give us a production for to satisfy the demand from the internal and external market, in which studied multiplication’s protocols in vitrio from the Uncaria tomentosa since of seeds as nodal segments in different hormonal concentrations from Citoquinina BAP; and it was perform in the laboratory for cultive of vegetables tissue of the Agrarian Sciences Faculty from the University National of San Martin-Tarapoto- Perú. The design employed was blocks completely to the chance. With factorial adjusment to 5 x 3 (concentrations resources of cultive agaínst nodal segments). During the process we made a lots of test in the sexual part like: germination, seed´s disinfestation, types of container used for the plantula's transfer, percentage from discard and live plants according the recipient, acclimatization in the moisture chamber and greenhouse, also since it did a following in the asexual part, to which it had to make excisions to the plantulas for cut joints and put in place in cultive's environments with different hormonal concentrations, that it was testing of the following way: number of callus, length of flows, main roofs numbers average, flow's numbers average, sub - cultive of flows as soon as percentage of vitrification, fenolization and dead. It´s an important mention that the research installed on january in the first fortnight on 2001 with the selection and wash of glass materials, equipment maintenance, following for the germination and development of the plantulas in prepare cultive's enviroments with purpose the choose mother plantulas for the cultive of tissues and finíshed with the handling and maintenace of the plants in the greenhouse.